The role of metastasis-directed therapy and local therapy of the primary tumor in the management of oligometastatic prostate cancer - Kim, Jongchan (Investig Clin Urol, 2017)
Oligometastasis has been proposed as an intermediate stage of cancer spread between localized disease and widespread metastasis. Oligometastatic malignancy is now being diagnosed more frequently as the result of improvements in diagnostic modalities such as functional imaging. The importance of oligometastasis in managing metastatic prostate cancer is that it is possible to treat with a curative aim by metastasis-directed or local therapy in selected patients. Many studies have shown that these aggressive treatments lead to improved survival in other oligometastatic malignancies. However, few studies have shown definitive benefits of metastasis-directed or local therapy in oligometastatic prostate cancer. Review of the available studies suggests that stereotactic radiotherapy (RT) of metastatic lesions in oligorecurrent disease is a feasible and safe modality for managing oligometastatic prostate cancer. Also, stereotactic RT can delay the start of androgen deprivation therapy. Many retrospective studies of metastatic prostate cancer have shown that patients undergoing local therapy seem to have superior overall and cancer-specific survival compared with patients not receiving local therapy. Ongoing prospective randomized trials would be helpful to evaluate the role of local therapy in oligometastatic prostate cancer.